Excess parameters of binary mixtures of tetrahydro- furfurylalcohol with cyclopentanol and 1-pentanol at (293.15, 303.15 and 313.15K) (Journal of the College of Basic Education, 2022)
Density and viscosity of the binary liquid mixtures of (THFA + cyclopentanol, THFA + 1-pentanol and cyclopentanol + 1-pentanol) have been measured as a function of composition range at 293.15, 303.15, 313.15K. From density and viscosity data, the values of excess molar volume (VE), the excess viscosity (ƞE) and excess Gibbs free energy of activation flow (∆G*E) were calculated and correlated by the Redlich-kister type function to derive the coefficients and estimate the standard error. Deviations from ideal behavior are discussed from the point of view of the molecular interactions present between the unlike molecules. As for all the binary mixtures studied the excess molar volume showed a positive deviation from ideal behavior at the three temperatures studied except for two points was negative at 293.15K for the system THFA+ cyclopentanol, while the excess viscosity and excess Gibbs free energy showed a negative from ideal behavior at the three temperatures.